2018
DOI: 10.1016/j.ejmech.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of phenylsulfonylfuroxan derivatives as gamma globin inducers by histone acetylation

Abstract: N-oxide derivatives 5(a-b), 8(a-b), and 11(a-c) were designed, synthesized and evaluated in vitro and in vivo as potential drugs that are able to ameliorate sickle cell disease (SCD) symptoms. All of the compounds demonstrated the capacity to releasing nitric oxide at different levels ranging from 0.8 to 30.1%, in vivo analgesic activity and ability to reduce TNF-α levels in the supernatants of monocyte cultures. The most active compound (8b) protected 50.1% against acetic acid-induced abdominal constrictions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Chelucci et al (2019) promising SCD treatment (Lanaro et al, 2018). Melo et al (2018) reported seven new phthalimide-furoxan conjugates (157-163) (Figure 13), and all the compounds were assessed for their antiplatelet properties. The research evaluated the prevalence of ADP and NO in platelet-based plasma using in vitro techniques.…”
Section: Phthalimides As Fetal Hemoglobin (Hbf) Inducersmentioning
confidence: 99%
See 1 more Smart Citation
“…Chelucci et al (2019) promising SCD treatment (Lanaro et al, 2018). Melo et al (2018) reported seven new phthalimide-furoxan conjugates (157-163) (Figure 13), and all the compounds were assessed for their antiplatelet properties. The research evaluated the prevalence of ADP and NO in platelet-based plasma using in vitro techniques.…”
Section: Phthalimides As Fetal Hemoglobin (Hbf) Inducersmentioning
confidence: 99%
“…Later in 2021, the same group reported new analogs (164-169) (Figure 13) for the treatment of SCD (Melo et al, 2018) values ranging from 0.3% to 6.3%. Treatment of CD34+ cells with compound 168 (at 2.5 µM), hydroxyurea (at 10 µM), and pomalidomide (at 1 µM) for 14 days showed significant induction of HbF by 168 compared to dimethyl sulfoxide induction (control).…”
Section: Phthalimides As Fetal Hemoglobin (Hbf) Inducersmentioning
confidence: 99%
“…This finding was consistent with the previous works published by our research group. [31][32][33] Therefore, the substitution of the N-acylhydrazone subunit was performed to overcome this inherent chemical instability. Similar to the Nacylhydrazone subunit-containing drug, the amide-containing drugs are also susceptible to hydrolysis, although at a much slower rate.…”
Section: Drug Designmentioning
confidence: 99%
“…All data were expressed within ± 0.4% of the theoretical values. Compounds 3, 9, 12, 14b, and 14e were prepared according to previously described methodologies [23][24][25][26][27]. Compounds 4p-x were synthesized according to previously described methods and the characterization data are not shown here [24].…”
Section: Chemistrymentioning
confidence: 99%
“…Then, compound (2) was treated with 4-hydroxybenzaldehyde and 1,8-diazabicyclo [5.4.0] undec7-ene (DBU) in a dichloromethane medium to provide compound (3) at a yield of 90% [21]. The amide-furoxan derivative ( 9) and benzofuroxan derivative (12) were obtained according to the previously described procedures [24,25]. Finally, the last step involved the coupling reaction of the aldehyde group in phenyl-furoxan (2), amide-furoxan ( 9), or benzofuroxan (12) within the appropriate hydrazides (5a-e; 6a-b) in medium containing ethanol and acetic acid at yields ranging from 82 to 96%, providing the Noxide compounds (4a-x) (Schemes 1 and 2).…”
Section: Chemistrymentioning
confidence: 99%